Reassessment of the status of some European and Asian Melitaea taxa described as subspecies of Melitaea phoebe ([Denis & Schiffermüller], 1775), with designations of lectotypes where appropriate (Lepidoptera: Nymphalidae) - Russell, Peter J. C.; Lukhtanov, Vladimir A.; Tennent, W. John (Zootaxa, 2022)
Morphological characters of value in distinguishing Melitaea phoebe from M. ornata are exemplified from photographs of specimens from sympatric and partially synchronic populations in the Russian Federation and Slovenia. Type material of a number of subspecies classified as M. phoebe have been examined and confirmed as being subspecies of M. phoebe or as subspecies of either M. ornata or M. telona. Larval and adult morphology of M. telona is very similar to those of M. ornata, making morphological separation difficult. Distribution of M. telona forms a major criterion for separation. Lectotypes are designated for amanica Rebel, 1917 and dorae Graves, 1925. The name enoch Higgins, 1941 is recognised as a distinct species and the names abbas Gross & Ebert, 1975 and zagrosi Tóth & Varga, 2011 synonymised with Melitaea enoch.